Appetite suppressants and primary pulmonary hypertension in the United Kingdom. Issue 6 (December 1995) - Thomas, S. H.; Butt, A. Y.; Corris, P. A.; Egan, J. J.; Higenbottam, T. W.; Madden, B. P.; Waller, P. C.
Abstract : OBJECTIVE--Amphetamine-like appetite suppressants, particularly fenfluramines, have been implicated in the aetiology of primary pulmonary hypertension. At one specialist centre in France 20% of patients with primary pulmonary hypertension had been exposed to fenfluramine. The prevalence of primary pulmonary hypertension associated with fenfluramines and other appetite suppressants in the United Kingdom is unknown. This study was performed to measure prior exposure to appetite suppressants in patients with primary pulmonary hypertension. SETTING--Heart lung transplantation centres in England. PATIENTS--United Kingdom residents with proven primary pulmonary hypertension referred for consideration of heart lung transplantation. METHODS--Case surveillance study, obtaining data from the hospital and general practitioner's notes and directly from the patients or their relatives. RESULTS--55 patients were identified. Drug histories were available from hospital records in all patients, from the general practitioner's notes in 51, and from the patients or relatives in 44. Of these, 3 female patients had been exposed to appetite suppressants (2 fenfluramine, 1 diethylpropion): 2 have since died. In each case exposure was brief and apparently predated the development of symptoms by several years. CONCLUSIONS--Exposure of patients with severe primary pulmonary hypertension to fenfluramine and other appetite suppressants is uncommon in the United Kingdom unlike in France, where most of the cases associating primary pulmonary hypertension with fenfluramine use have originated. This may reflect more conservative prescribing of these agents in the United Kingdom.